The Results of Management of Distal End Radius Fractures by Various Modalities - Mansi J Patel; Dhyey Baldha; Aaksh Nareshbhai Koladiya; Lalit Bambhaniya; Utkarsh Panchal; Tejas Jogi; Ishani Patel; Neel Bhavsar (Journal of Orthopedic and Spine Trauma)
Introduction: Distal end radius fractures constitute 16-20% of all fractures. Extra-articular fractures are managed with closed reduction and casting, while intraarticular fractures require more invasive treatment due to instability and conservative treatment complications. Despite extensive research, the optimal treatment for distal end radius fractures remains unclear, prompting ongoing comparative studies.